TAXONOMY OF BEGONIA ALBOMACULATA AND DESCRIPTION OF TWO NEW SPECIES ENDEMIC TO PERU - Moonlight, P. W.; Hughes, M.; Tebbitt, M. C. (Edinburgh Journal of Botany, 2017)
Begonia mayasiana L.B.Sm. & B.G.Schub. is shown to be synonymous with Begonia albomaculata C.DC. An emended description and lectotypification of Begonia albomaculata is provided, and the species is recorded from the Peruvian regions of Amazonas, Loreto, San Martín, Huánuco and Ucayali; the Brazilian state of Acre; and the Ecuadorian province of Pastaza. The use of the name Begonia albomaculata in the Flora of Ecuador and related publications is a misapplication, and the specimens cited there represent an undescribed taxon closely related to Begonia tiliifolia C.DC., described in a companion paper in this volume. Taxonomic study of Begonia albomaculata prompted a re-evaluation of related Andean species. As a result, two further new species were identified, and Begonia longimaculata Irmsch. and Begonia maynensis A.DC. were found to be conspecific. The two new species are described as Begonia chemillenensis Moonlight sp. nov. and Begonia scorpiocaulis Moonlight & Tebbitt sp. nov., and are known only from the Pasco and Huánuco regions and the Madre de Dios region of Peru, respectively. Begonia longimaculata Irmsch. is newly treated here as a synonym of B. maynensis A.DC.
Keywords: Begonia albomaculata; Begonia longimaculata; Begonia mayasiana; Begonia maynensis; Begonia sect. Knesebeckia; Brazil; Ecuador; Peru